Impact of frailty on super elderly patients with peripheral artery disease from the I-PAD 3 year registry. (25th November 2020) - Nishikawa, K; Nagae, A; Miura, T; Katoh, T; Kanzaki, Y; Abe, N; Yokota, D; Yanagisawa, T; Senda, K; Wakabayashi, T; Oyama, Y; Okina, Y; et al.
Abstract: Background: Unlike age, frailty is often not taken into account in treatment indications of Endovascular treatment (EVT). One of the reason is that there was little known the relationship between frailty and the outcome of EVT for super elderly patients with peripheral artery disease (PAD). We investigate impacts of frailty on the super elderly patient prognosis who underwent EVT. Purpose: To investigate impacts of frailty on the super elderly patient prognosis who underwent EVT. Methods: From August 2015 to July 2016, 335 consecutive patients who underwent EVT were enrolled in the I-PAD registry from 7 institutes in Nagano prefecture. Among them, we selected and analyzed 91 super elderly PAD patients (≥80 years-old) and divided them into two groups:those with moderate or higher frailty (Clinical Frailty Scale (CFS) ≥6, n=28) and those without (CFS ≤5, n=63). The primary endpoints were cardiovascular death and major adverse cardiovascular and limb events (MACLE), defined as a composite of cardiovascular death, myocardial infarction, stroke, admission for heart failure, major amputation and revascularization. Results: The median follow-up period was 2.7 years. Freedom rate from cardiovascular death and MACLE were significantly lower among patients with moderate or higher frailty than among those without (47.0% vs. 58.0%, P=0.03; 39.1% vs. 68.5%, P<0.01). Conclusion: The prognosis of super elderly patients with moderate or higher frailty is worse than those without. Funding Acknowledgement: Type of funding source: None